2023
DOI: 10.3389/frobt.2022.1059026
|View full text |Cite
|
Sign up to set email alerts
|

The science of soft robot design: A review of motivations, methods and enabling technologies

Abstract: Novel technologies, fabrication methods, controllers and computational methods are rapidly advancing the capabilities of soft robotics. This is creating the need for design techniques and methodologies that are suited for the multi-disciplinary nature of soft robotics. These are needed to provide a formalized and scientific approach to design. In this paper, we formalize the scientific questions driving soft robotic design; what motivates the design of soft robots, and what are the fundamental challenges when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…This could be achieved by using lighter materials or by tapering the arm diameter and mass along its length. In addition, pneumatic actuation is not practical for all applications, so alternative actuation and stiffening technologies could be explored, such as dielectric elastomer actuators (55,56), twisted string actuators (57,58), and cable-driven approaches (35,59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be achieved by using lighter materials or by tapering the arm diameter and mass along its length. In addition, pneumatic actuation is not practical for all applications, so alternative actuation and stiffening technologies could be explored, such as dielectric elastomer actuators (55,56), twisted string actuators (57,58), and cable-driven approaches (35,59).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many examples of structures and actuators that enable robots to actively vary the compliance of their bodies, there is a need for principled modeling, design, and control approaches for effectively implementing variable compliance to achieve desired performance goals. Toward that aim, Stella et al ( 35 ) presented a strategy for controlling the pose and physical stiffness of a soft robot arm to achieve a desired compliance at the point of contact with the environment. The approach was validated in simulation and on a real tendon-driven variable stiffness manipulator, enabling the robot to successfully perform a peg-insertion task.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al (2019) showed a soft robot for MIS embedded with responsive materials that can be remotely controlled to perform delicate procedures, reducing invasiveness and recovery time 12). Advances in sustainable manufacturing, design, and materials are driving soft robotics toward impactful solutions to achieve SDGs and aid the climate transition (Stella and Hughes, 2023).…”
Section: Sustainable Manufacturing Processesmentioning
confidence: 99%
“…Rigid robots excel at precision and repetitive tasks but typically fall short in environments where compliance, robustness to disturbances, or energy efficiency is crucial ( 1 ). Therefore, researchers aim to mimic natural organisms, which are well adapted to operate effectively in unstructured environments ( 2 ).…”
Section: Introductionmentioning
confidence: 99%